Coupling Fe3C Nanoparticles and N‐Doping on Wood‐Derived Carbon to Construct Reversible Cathode for Zn–Air Batteries. Issue 26 (29th May 2022) - Cao, Mengmeng; Liu, Yanyan; Sun, Kang; Li, Heng; Lin, Xiaoqian; Zhang, Pengxiang; Zhou, Limin; Wang, Ao; Mehdi, Sehrish; Wu, Xianli; Jiang, Jianchun; Li, Baojun
Abstract: Electrochemical reduction of oxygen plays a critical role in emerging electrochemical energy technologies. Multiple electron transfer processes, involving adsorption and activation of O2 and generation of protons from water molecules, cause the sluggish kinetics of the oxygen reduction reaction (ORR). Herein, a double‐active‐site catalyst of Fe3 C nanoparticles coupled to paulownia wood‐derived N‐doped carbon (Fe3 C@NPW) is fabricated via an active‐site‐uniting strategy. One site on Fe3 C nanoparticles contributes to activating water molecules, while another site on N‐doped carbon is responsible for activating oxygen molecules. Benefiting from the synergistic effect of double active sites, Fe3 C@NPW delivers a remarkable catalytic activity for ORR with a half‐wave potential of 0.87 V (vs. RHE) in alkaline electrolyte, outperforming commercial Pt/C catalyst. Moreover, zinc–air batteries (ZABs) assembled with Fe3 C@NPW as a catalyst on cathode achieve a large specific capacity of 804.4 mA h gZn −1 and a long‐term stability of 780 cycles. The model solid‐state ZABs also display satisfactory performances with an open‐circuit voltage of 1.39 V and a high peak power density of 78 mW cm −2 . These outstanding performances reach the level of first‐rank among the non‐noble metal electrode materials. This work offers a promising approach to creating double‐active‐site catalysts by the active‐site‐uniting strategy for energy conversion fields. Abstract : A Fe3 C@NPW electrode composed of Fe3 C nanoparticles (NPs) and paulownia wood (PW)‐derived N‐doped carbon is manufactured by an active‐site‐uniting strategy. One site on Fe3 C nanoparticles contributes to activating water molecules, while another site on N‐doped carbon is responsible for activating oxygen molecules. Benefiting from the synergistic effect of double active sites, Fe3 C@NPW exhibits outstanding catalytic activities in a zinc–air battery.